Pengaruh Citra Merek dan Kepercayaan Merek Terhadap Loyalitas Pelanggan Smartphone Samsung: Studi pada Mahasiswa Fakultas Ekonomi Universitas Sriwijaya - Riovaldo Indrajaya Liga; Ahmad Maulana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The scientific goal of this study aims to understand how brand image and brand trust simultaneously and partially influence customer loyalty. This study collected primary data by administering questionnaires to a sample size of 100 respondents. The sampling technique used is purposive sampling technique. The analytical approach applied includes the F-test, T-test, multiple linear regression, and R-squared test. This research provides conclusions brand image and brand trust simultaneously exert a notable influence on customer loyalty. Partially, brand image and brand trust affsect customer loyalty. Multiple linear regression analysis gives the conclusions of brand image variables as the dominant variable influencing customer loyalty.